Heart transplantation after total artificial heart bridging—Outcomes over 15 years. Issue 11 (5th September 2022) - Chen, Qiudong; Chan, Joshua; Akhmerov, Akbarshakh; Roach, Amy; Emerson, Dominic; Megna, Dominick; Catarino, Pedro; Moriguchi, Jaime; Chang, David; Kittleson, Michelle; Geft, Dael; Kobashigawa, Jon; et al.
Abstract: Background: Data are limited on outcomes after heart transplantation in patients bridged‐to‐transplantation (BTT) with a total artificial heart (TAH‐t). Methods: The UNOS database was used to identify 392 adult patients undergoing heart transplantation after TAH‐t BTT between 2005 and 2020. They were compared with 11 014 durable left ventricular assist device (LVAD) BTT patients and 22 348 de novo heart transplants (without any durable VAD or TAH‐t BTT) during the same period. Results: TAH‐t BTT patients had increased dialysis dependence compared to LVAD BTT and de novo transplants (24.7% vs. 2.7% vs. 3.8%) and higher levels of baseline creatinine and total bilirubin (all p  < .001). After transplantation, TAH‐t BTT patients were more likely to die from multiorgan failure in the first year (25.0% vs. 16.1% vs. 16.1%, p  = .04). Ten‐year survival was inferior in TAH‐t BTT patients (TAH‐t BTT 53.1%, LVAD BTT 61.8%, De Novo 62.6%, p  < .001), while 10‐year survival conditional on 1‐year survival was similar (TAH‐t BTT 66.8%, LVAD BTT 68.7%, De Novo 69.0%, all p  > .20). Among TAH‐t BTT patients, predictors of 1‐year mortality included higher baseline creatinine and total bilirubin, mechanical ventilation, and cumulative center volume <20 cases of heart transplantation involving TAH‐t BTT (all p  < .05). Conclusion: Survival after TAH‐t BTT is acceptable, and patients who survive the early postoperative phase experience similar hazards of mortality over time compared to de novo transplant patients and durable LVAD BTT patients.